The role of military directors in holding the CEO accountable for poor firm performance - Pavićević, Stevo; Keil, Thomas (Strategic Management Journal, 2025)
Abstract Research Summary Why do some boards of directors dismiss the CEO when a firm performs poorly, while others do not? We argue that military directors—outside directors with military backgrounds—on the board increase the likelihood of CEO dismissal under low‐performance conditions. Military service instills a lifelong system of values and beliefs related to accountability—the obligation to accept responsibility for one's own actions and outcomes—which leads military directors to attribute low performance to the CEO and hold the CEO strictly accountable for such performance. This argument is supported by extensive quantitative data on CEO dismissal in publicly listed firms and qualitative data obtained from interviews with military directors who have served on boards of those firms. Managerial Summary Military directors—outside directors with military backgrounds—frequently occupy seats on the boards of publicly listed firms in the United States. Military service instills an enduring system of values and beliefs rooted in accountability, which, we argue, makes military directors more inclined to attribute performance shortfalls to the CEO and advocate for more rigorous CEO accountability, resulting in CEO dismissal. Our argument is supported by quantitative data on CEO dismissals within publicly listed firms and qualitative data derived from interviews with military directors who have served on boards of those firms. Our findings underscore that principles ingrained via military service may influence corporate governance, particularly one of its core components: executive accountability.